Pengaruh Indeks Harga Saham Syariah Internasional dan Variabel Makro Ekonomi Terhadap Jakarta Islamic Index - Beik, Irfan Syauqi; Fatmawati, Sri Wulan (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2014)
The Impact of International Islamic Stock Market and Macroeconomic Variables Towards Jakarta Islamic Index (JII) This research atempts to examine the impact of international Islamic stock market and macroeconomic variables towards Jakarta Islamic Index (JII). By using Vector Error Correction Model (VECM) as the method, this research utilizes time series monthly data from January 2007 to October 2012. The finding shows that JII is positively significantly affected by DJIEU, DJIMY and IPI, and it is negatively significantly affected by DJIJP, IMUS, M2 and SBIS.JII reaches its stability condition fastest when dealing with money supply shock. This study recommends: strengthening coordination between monetary authority and financial services authority, strengthening real sector of the economy, minimizing the influence of interest Rate towards Islamic financial market, and developing early warning system to anticipate financial crises. DOI:10.15408/aiq.v6i2.1228